Cultivares crioulas de milho (Zea mays, L.) em sistema de produção orgânico desempenho agronômico das plantas e composição química das sementes - Câmara, Roberto José (2005)
This work had as objective to characterize and to evaluate six to cultivate Creoles and two hybrids of maize, in organic system of production. The sowing was carried through in 30 of October of 2003, in an area of organic agriculture certified, in the farm Is Jose, property of Mr. Silvério Guerini, in the city of Is Miguel of the Iguaçu - Paraná, situated in the Indianópolis community between the geographic coordinates, latitude 25º 31" 10' S and longitude 54º 14"39' W, altitude 260 meters. The used experimental delineation was of blocks unexpected with three repetitions. They had been used to cultivate them Creole of maize (Zea mays L.) Pixurum 5, Asteca, Ipanema, Palha Poxa, Sol da Manhã and BRS - 4150 and Pioneer hybrids 30F44 HS and Agroeste - 3466 HD. The Creole seeds had been acquired together to the agriculturists of the Agricultural Sitting of Caxias Jump in the region of Cascavel - Paraná. The sowing was carried through in area previously cultivated with White Lupin (Lupinus albus), without fertilizer addition some for occasion of the sowing and during the development of the culture. Only practical the cultural ones had been the to thin of plants and a manual weeding. The evaluated 0 variable had been the following ones: the height of the plant (AP), b) height of the insertion of the spike (AIE), c) feminine bloom (FF), d) plants laid flat and broken by parcel (PAQ), e) I number total of spikes (NTE), f) finally stand (EF), g) index of spikes (IC), h) relative position of the spike in the plant (PREP), i) index of prolific dade (PROL), j) productivity of grains (PG), k) mass of a thousand seeds (MMS), l) starch, m) oil n) tear of protein. The gotten results allow to conclude that to cultivate them Pixurum 5, Sol da Manhã and BRS - 4150 are to cultivate suitable to this e region present good productivity. To cultivate them Asteca, Ipanema and Palha Roxa had been less productive.